What you don't know can't help you: pension knowledge and retirement decision making - Ann Huff Stevens; Sewin Chan (University of California, Department of Economics, 2005)
This paper provides an answer to an important empirical puzzle in the retirement literature: while most people know little about their own pension plans, retirement behavior is strongly affected by pension incentives. We combine administrative and self-reported pension data to measure the retirement response to actual and perceived financial incentives. While virtually all recent empirical work has relied on administrative- or employer-reported data, we document an important role for self-reported pension data in determining retirement behavior. Well-informed individuals are five times more responsive to pension incentives than the average. In contrast, ill-informed individuals respond to their own misperceptions of the incentives rather than being unresponsive to any measured incentives.
Keywords: 330